Progress and perspectives on two-dimensional silicon anodes for lithium-ion batteries - Han Zhao; Fan Yang; Chongxing Li; Tong Li; Shuxian Zhang; Chengxiang Wang; Zhiwei Zhang; Rutao Wang (ChemPhysMater, 2023)
Silicon (Si) anodes with extremely high theoretical capacities are considered indispensable for next-generation high-energy lithium-ion batteries (LIBs). However, several intractable problems, including pulverization, poor electrical contact, and continuous side reactions caused by the large volume change of Si during lithiation/delithiation, lead to a short cycle life and poor rate capability, thus hindering the commercial use of Si anodes in LIBs. Two-dimensional (2D) Si with a unique graphene-like structure has a short ion diffusion pathway, small volume change during lithiation, and efficient redox site utilization, making it more promising than bulk Si or Si with other versatile structures for use in LIBs. Theoretical analysis demonstrated that the low energy barrier on the surface of 2D Si accelerates the transport of Li+. However, the issues surrounding 2D Si, including the tedious and user-unfriendly synthesis, ease of restacking, and atmospheric sensitivity, limit its practical applications, which are discussed in this review. Furthermore, possible solutions to these remaining challenges and new directions are provided, with the aim of designing practical and high-performance 2D Si anodes for next-generation LIBs.